Avis Spirituels Pour Servir A La Sanctification des Ames (Ancienne Maison Charles Douniol, 1899)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 18.Bookworm (Only Cover)

Boletim Official do Governo da Provincia de Macau (IMPRENSA NACIONAL, 1899)
Stamp of St. Joseph Seminary
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage

Officium Parvum, Beatae Mariae Virginis Cum Cantu Ex Antiphonario Romano (Ratisbonae, Romae, et Neo Eboraci, 1899)
Keywords: 1.Conservation 保護; 18.Bookworm

Sacrosancti et Oecuenici, Concilii Tridentini (Apud. A. Jouby Et Roger, 1899)
Stamp
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 2.Damage

Sacrosancti et Oecumenici, Concilii Tridentini (Apud A. Roger et Chernoviz Bibliopolas, 1899)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 18.Bookworm; 2.Damage

Emmanuelis Alvari, e Societate Jesu, Institutionum grammaticaticarum liber tertius - Alvares, Manuel (typis Samuelis Müller, Universitatis Viennensis typographi, 1899)
Keywords: latinščina slovnica

Manuel Biblique, Cours D'ecriture Sainte - Bacuez, L (A. Roger et F. Chernoviz, Editeurs, 1899)
Signature, Stamp of Saint Joseph Seminary
Keywords: 1.Conservation 保護; 10.Cover Damage; 2.Damage; 6.Yellowing 變黃

Les Peres de L'eglise Leur vie et Leurs Oeuvres - Bardenhewer, O. (Bloud et barral, Editeurs, 1899)
Stamp
Keywords: 1.Conservation 保護; 18.Bookworm; 6.Yellowing 變黃

Les Peres de L'eglise Leur vie et Leurs Oeuvres - Bardenhewer, O. (Bloud et barral, Editeurs, 1899)
Stamp
Keywords: 1.Conservation 保護; 18.Bookworm; 6.Yellowing 變黃

Dictionnaire universel de la pensée: alphabétique, logique et encyclopédique ; classification naturelle et philosophique des mots, des idées et des choses - Blanc, Élie (Vitte, 1899)
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; 22.signature; Biographies; Condition: Fair; Dictionaries; Hard Cover; Philosophers, Modern; Philosophers, Modern Biography; Philosophes modernes Biographies; Philosophie Dictionnaires français; Philosophy

Dictionnaire universel de la pensée: alphabétique, logique et encyclopédique ; classification naturelle et philosophique des mots, des idées et des choses - Blanc, Élie (Vitte, 1899)
Keywords: Biographies; Dictionaries; DictionariesDictionariesChinese language Dictionaries English; DictionariesDictionariesChinese language Dictionaries French; DictionariesDictionariesDictionaries; DictionariesDictionariesDutch language Dictionaries English; DictionariesDictionariesEncyclopedias and dictionaries; DictionariesDictionariesEncyclopedias and dictionaries Specimens; DictionariesDictionariesEnglish language 20th century Dictionaries; DictionariesDictionariesEnglish language 20th century Dictionaries Chinese; DictionariesDictionariesEnglish language Australia Dictionaries; DictionariesDictionariesEnglish language Dictionaries; DictionariesDictionariesEnglish language Dictionaries Chinese; DictionariesDictionariesEnglish language Dictionaries Dutch; DictionariesDictionariesEnglish language Dictionaries French; DictionariesDictionariesEnglish language Dictionaries Latin; DictionariesDictionariesEnglish language Dictionaries Portuguese; DictionariesDictionariesEnglish language Dictionaries Spanish; DictionariesDictionariesEnglish language Idioms - Dictionaries; DictionariesDictionariesEnglish language Idioms Dictionaries; DictionariesDictionariesEnglish language New words Dictionaries; DictionariesDictionariesEnglish language Orthography and spelling Dictionaries; DictionariesDictionariesEnglish language Pronunciation Dictionaries; DictionariesDictionariesEnglish language--Dictionaries--Spanish; DictionariesDictionariesFrench language Dictionaries Chinese; DictionariesDictionariesFrench language Dictionaries English; DictionariesDictionariesFrench language French-English, English-French dictionaries; DictionariesDictionariesItalian language Dictionaries; DictionariesDictionariesLatin language Dictionaries English; DictionariesDictionariesLatin language Dictionaries French; DictionariesDictionariesMultilingual dictionaries; DictionariesDictionariesPortuguese language - Portuguese & English dictionaries; DictionariesDictionariesPortuguese language Dictionaries Chinese; DictionariesDictionariesPortuguese language Dictionaries English; DictionariesDictionariesSpanish language Dictionaries English; DictionariesDictionariesSpanish language--Dictionaries--English; DictionariesDictionariesdictionaries; DictionariesDictionariespolyglot dictionaries; Philosophers, Modern; Philosophers, Modern Biography; Philosophes modernes Biographies; Philosophie Dictionnaires français

Psychologia rationalis: sive, Philosophia de anima humana : in usum scholarum - Boedder, Bernard (Cursus philosophicus, 1899)
Keywords: Condition: Fair; Filosofische antropologie; Hard Cover; Philosophy; Psychologie; Psychology; Teaching; psychology

Diccionário de synonymos da língua portugueza - Brunswick, Henry (Francisco Pastor, 1899)
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; Condition: Fair; Dictionaries; Hard Cover; Língua portuguesa Sinónimos [Dicionários]; languages

Les Apparitions de Lourdes, Souvernirs Intimes D'un Temoin - Estrade, J. B. (Alfred Mame et Fils, Editeurs, 1899)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 2.Damage; 6.Yellowing 變黃

Santo Antonio de Lisboa - F. A. Carlos das Neves (Largo dos Loyos, 1899)
Stemp of St. Joseph Seminary
Keywords: Poor

Bibliotheca, Canonica Iusidica Moralis Theologica - Ferraris, F. Lucii (Ex Typographia Polyglotta, 1899)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 18.Bookworm; 2.Damage; 6.Yellowing 變黃

Catecismo de Perseveranca - Gaume, J. (Livraria Chardron, 1899)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 18.Bookworm; 6.Yellowing 變黃

Catecismo de Perseveranca - Gaume, J. (Livraria Chardron, 1899)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 18.Bookworm; 6.Yellowing 變黃

Commentarius in Numberos - Hummelauer, Francisco de (Summptibus P. Lethielleux, Editoris, 1899)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 15.Stain 污漬; 18.Bookworm; 2.Damage

Commentarius in Actus Apostolorum - Knabenbauer, Iosepho (sumptibus p. lethieleux, editoris, 1899)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 18.Bookworm; 6.Yellowing 變黃

O Sagrado Goragao de Jesus - L. M. A. M. (Typographia da Casa Catholica, 1899)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 18.Bookworm; 2.Damage; 6.Yellowing 變黃

A Voz do Evangelho - Malhão (1899)
sign
Keywords: 18.Bookworm; Fair

Les Erreurs Sociales du Temps Present - Meric, Elie (Ancienne Maison Charles Douniol, 1899)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 10.Cover Damage; 2.Damage

Vida Intima com Jesus ou Meditacoes Para Pessoas Piedosas - Nevers, Estevao de (Livraria Catholica, 1899)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 18.Bookworm; 2.Damage

Noções de hygiene e medicina pratica para uso dos alumnos do seminario diocesano de Macau - Professor do seminario diocesano de Macau (Typographia do Seminario, 1899)
lisongeado com a dedicatoria deste folheto, como trabalho sientifico, deixa tudo a desejar e como comperdio de noções praticas. podera valer, quando muito, por prova da boa vontade do auctor, que desejou por este meio valer de promplto a uma necessidade de occasião. crara no Seminario Diocesano a cadeira de noções de hygiene e medicaina pratica e incumbria-me da regencia dessa cadeira. o anno lectivo começara e urgia que os alumnos que findaram este anno o curso theologico aproveitassem ja estas noções, que porderiam ser.lhes de alguma utilidade; não havia em Macau livros a venda que se pudesse adequar ao fim proposto, e o mandar vil-os do reino tomaria muito tempo e algum dinheiro; a consequencia destas circumstancias foi que tive de elaborar as licções dia a dia, para as ir expondo aos meus alumnos. Occorreu-me então que as licções produziriam por ventura melhor proreito, se fossem sendo impressas a proporção que eram elaboradas e expostas. Uma coisa é ouvir uma prelecção em que se enuncia um certo numero de principios, nem sempre muito connexos e mnemonicos, e fixar dali tudo o que nelles ha de util e proveitoso; outra coisa é ter deante de si o resumo escripto desses principios e poder com elles avivar a memoria das licções ouvidas. E depois, outra ideia surgiu no meu espirito a reforçar a da elaboração deste pequene livro, é que o dinheiro que Seminario Diocesano ou os meus alumnos haviam de dispender na acquisição dum comprendiu, elementar de hygiene e medicina, mandado vir do reino, podia muito bem ter mais benefica applicação, revertendo em favor desse santo instituto que achi esta salvando, diariamente, o corpo e a alma a tantos innocentes, que a miseria ou. o desamor dos paes arroja a via publica. As ideias são como as cerejas, nunca réem sos. Desde que se tractava dum objecto util aos alumnos do Seminario, que são os filhos dilectos de V. Ex. Rev. Deste que esse objecto podia, ao mesmo tempo, servir de pretexto a uma esmola, que fosse, ainda que ao de leve, minorar as difficuldades com que lucta o asylo da Santa Infancia para manter as suas portas permanentemente abertas as victimas do indifferentismo e da fome. dadas estas duas circumstancias, a dedicatoria do modesto trabalho impunha.se ao auctor. foi a causa directa do apparecimento deste livrinho e a indirecta dos fructos que elle puder produzir, pertence-lhe, portanto. Poderia faltar-me a coragem de dedicar a V. Ex. Rev, que é um homen de letras, um trabalho modesto, sem valor intrinseco; para o que me não falta coragem é para dar a Pedro o que e de Pedro.
Keywords: China Macau (Special Administrative Region); Macau; Saint Joseph Seminary; Seminarians Health and hygiene China Macau (Special Administrative Region); Seminarians Medical care China Macau (Special Administrative Region)

Novena, Triduo e Oracoes em Honra da B. Margarida Maria Alacoque - R. R. M (Typographia do Seminario, 1899)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 15.Stain 污漬; 18.Bookworm

The Navitivity of ou Lord Jesus Christ - Richard, George (Burns & Oates, 1899)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 18.Bookworm; 2.Damage

O Materialismo em Face da Sciencia - Santana, Manuel Fernandes de (1899)
Keywords: 1.Conservation 保護; 2.Damage

La Devotion au Sacre Coeur de Jesus - Schmude, R. P. (Desclee, De Brouwer & Cie, 1899)
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 2.Damage

AB URBE CONDITA - T. LIVII (Ex Typographia nationali, 1899)
Keywords: 2.Damage; Condition: Fair; Hard Cover

Obras Completas, Padre Antonio Vieira, Sermoes - Vieira, António (Colecção de clássicos Sá da Costa, 1899)
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; 22.stamp; Catholic Church; Catholic Church Sermons; Condition: Fair; Religion; Sermons; Sermons, Portuguese; Église catholique Sermons

Obras Completas, Padre Antonio Vieira, Sermoes - Vieira, António (Colecção de clássicos Sá da Costa, 1899)
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; Catholic Church; Catholic Church Sermons; Condition: Fair; Religion; Sermons; Sermons, Portuguese; Église catholique Sermons

Obras Completas, Padre Antonio Vieira, Sermoes - Vieira, António (Colecção de clássicos Sá da Costa, 1899)
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; Catholic Church; Catholic Church Sermons; Condition: Fair; Hard Cover; Religion; Sermons; Sermons, Portuguese; Église catholique Sermons

Obras Completas, Padre Antonio Vieira, Sermoes - Vieira, António (Colecção de clássicos Sá da Costa, 1899)
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; 22.stamp; Catholic Church; Catholic Church Sermons; Condition: Fair; Hard Cover; Religion; Sermons; Sermons, Portuguese; Église catholique Sermons

Obras Completas, Padre Antonio Vieira, Sermoes - Vieira, António (Colecção de clássicos Sá da Costa, 1899)
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; Catholic Church; Catholic Church Sermons; Condition: Fair; Religion; Sermons; Sermons, Portuguese; Église catholique Sermons

Obras Completas, Padre Antonio Vieira, Sermoes - Vieira, António (Colecção de clássicos Sá da Costa, 1899)
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; Catholic Church; Catholic Church Sermons; Condition: Fair; Religion; Sermons; Sermons, Portuguese; Église catholique Sermons

Obras Completas, Padre Antonio Vieira, Sermoes - Vieira, António (Colecção de clássicos Sá da Costa, 1899)
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; Catholic Church; Catholic Church Sermons; Condition: Fair; Religion; Sermons; Sermons, Portuguese; Église catholique Sermons

Rudiments de parler chinois: dialect du [Ho Kien Fu] - Wieger, Léon (Imprimerie de la Mission catholique, 1899)
Keywords: 10.Cover Damage; 2.Damage; China; Chinese language; Chinese language Readers; Chinese literature; Chinese literature Translations into French; Condition: Fair; French literature Translations from Chinese; Readers (Publications); Translations; languages

Rudiments de parler chinois: dialect du [Ho Kien Fu] - Wieger, Léon (Imprimerie de la Mission catholique, 1899)
《汉语入门》（Rudiments de Parler Chinois: Dialecte Du）是法国耶稣会士戴遂良（Léon Wieger，1856-1933）以清末河间府方言为基础编写的汉语口语教材。该书共两册，分别于 1895 和 1899 年出版，是作者计划出版的十二卷本丛书“汉语汉文入门” 的第一卷（刘亚男，2017）。戴遂良于 1887 年来华，1933 年逝世于献县。在华 46 年间，他一直在直隶献县教区传教，一生绝大多数时间都居住在献县，仅 1911 年离开中国出行日本和欧洲。1905 年，根据沙畹的提名，戴遂良的《汉语入门》获得法国汉学研究最高奖项——儒莲奖。1919 年，他被巴黎国际历史学协会评为“最有影响的汉学家”之一（谢海涛，2013）。
Keywords: 10.Cover Damage; 2.Damage; China; Chinese language; Chinese language Readers; Chinese literature; Chinese literature Translations into French; Condition: Fair; French literature Translations from Chinese; Readers (Publications); Translations; languages

Nuevo diccionario portugués-español y español-portugués, con la pronunciación figurada en ambas lenguas - Wildik, Vizconde (Garnier, 1899)
Keywords: 10.Cover Damage; 2.Damage; Condition: Fair; Dictionaries; Hard Cover; Portuguese language; Portuguese language Dictionaries Spanish; Spanish language; Spanish language Dictionaries Portuguese; languages

La Palestine d'aujourd'aui ses sanctuaires ses localites bibliques and historiques - Zanecchia, R. P. Dominique (P. Lethielleux, Libraire-Editeur, 1899)
Keywords: Good